Spatial patterns of genetic variation in the Iberian honey bee hybrid zone: a comparison between mitochondrial and nuclear DNA - Pinto, M. Alice (2012)
The Iberian honey bee (Apis mellifera iberiensis) has been intensely surveyed for genetic variation with different markers ranging from morphology, allozymes, mitochondrial DNA (mt DNA), to microsatellites. Some of these markers have revealed non-concordant complex patterns of genetic variation, which led scientists to evoke competing hypotheses for the origin of Iberian honey bees. While complex patterns and underlying historical processes are typical of hybrid zones, the use of more powerful molecular and analytical tools and the fine-scale sampling promised to help dissecting the complexities of the Iberian hybrid zone. In this study, we conducted a genome-wide sampling by genotyping over 384 SNPs (single nucleotide polymorphisms) and sequenced an intergenic fragment of the mt DNA in 711 georeferenced honey bee samples collected across three North-South transects in the Iberian Peninsula. Both mt DNA and SNP datasets were analyzed using spatial tools to represent the structure generated by both types of molecular markers. We found concordant spatial patterns between markers which led to rejection of the standing hypothesis of recent human introductions and selection as the processes shaping Iberian honey bees patterns. This study shows that the fine-scale genomic and spatial analyses can reveal patterns which would otherwise had been undetected.